SRM-MS Method Development for Hepcidin-25 Peptide. (14th June 2018) - Cho, Kyung-Cho; Cho, Byoung-Kyu; Jung, Jin Woo; Lee, Ye Ji; Lee, Eun Bong; Yi, Eugene C.
Abstract : As advanced mass spectrometry- (MS-) based hepcidin analysis offers to overcome the limitations in analytical methods using antihepcidin, further improvement of MS detection sensitivity for the peptide may enhance the diagnostic value of the hepcidin for various iron-related disorders. Here, improved MS detection sensitivity of hepcidin has been achieved by reducing the disulfide bonds in hepcidin, by which proton accessibility increased, compared to the intact hepcidin peptide. Comparing the ionization efficiencies of reduced and nonreduced forms of hepcidin, the reduced form of hepcidin showed an increase in ionization efficiency more than two times compared to the nonreduced form of hepcidin. We also demonstrated improved detection sensitivity of the peptide in SRM assay. We observed a significant improvement of detection sensitivity at the triple-quadrupole MS platform, that the ionization efficiency increased at least twice more, and that the limit of detection (LOD) increased more than 10 times in the concentration ranges of 1 fmol to 10 fmol of hepcidin. In this study, we demonstrated the usefulness of the hepcidin modification for overall enhancement of the ionization efficiencies of the hepcidin peptide in the MS-based quantitative measurement assay.